A Study on Indian Mythology as Literature: Exploring the Influence of Hindu Mythology in Indian Literature (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Novel as a genre might not inherently be an Indian innovation but as a form, it has favored Indian authors who have embraced it and adapted it skillfully to their creative intent. These native novelists have strengthened their function as an essential literary instrument with the aid of Hindu mythology. Whether belonging to the pre-independence era or to the post-independence period, the riches of this perpetual pool of a country with an ancient cultural historical heritage was extremely tempting for any poet. This paper aims to include a brief study in the work of Indian poets, including Bankim Chandra Chattopadhyay, Raja Rao and R K Narayan, of Hindu mythology as a literary method. It also aims at addressing the Hindu mythology as a credible source and influential instrument for the personal and political problem of these people. Guy, still returns to the past in pursuit of answers. Culture, theory and theory are perfect origins to both responses. To discover the absolute truth, man starts a trip to the place he abandoned years before. Authors also have an unusual connection with their works and their culture's myths and legends.The usage of Hindu myths is a literary practice of Indian English literature. Indian myths have a long tradition that addresses all sorts of societal, political and theological concerns. These magnificent stories give writers the space to place their thoughts in a great way.